Ecotourism in Florida: Letting Nature Work For You - Mechelle N. Best; Taylor V. Stein (EDIS, 2007)
Circular 1517, a 15-page full-color catalog compiled by Mechelle N. Best and Taylor V. Stein, provides case studies of ten private nature-based tourism businesses throughout Florida. Each case study provides a brief description of the site, presents the start-up and operational challenges encountered, and highlights the lessons learned by the various owners/operators. Finally, the benefits to the owner/manager and the reasons why they stick with it are provided. Published by the UF School of Forest Resources and Conservation, September 2007.